Correlation between serum Ca, Mg, Zn & Cu and hypertension in pre-eclampsia - Zaater, Mahmoud K (African Journal of Nephrology, 2023)
Pre-eclampsia is potentially preventable, but potentially morbid and/or a fatal disease. The aim of this work is to study serum levels of copper, zinc, calcium and magnesium in pregnant patients with pre-eclampsia. 15 patients diagnosed as pre-eclampsia "patient group" (group 1) and two age matched control groups [8 essential hype1tension non pregnant women (group 2)] and [8 normotensive pregnant women (group3 )] were studied. All persons were subjected to full history with special attention to past history of hypertension and renal disease, clinical examination, routine laboratory investigation and estimation of serum levels of copper, zinc, calcium and magnesium by spectrophotometer method. The resul!s revealed significant increase of serum uric acid in group1 (6.64 ± 0.62 mg%) vs. (3 ± 0.55 mg%) in group2 and (4.12 ± 0.5 mg%) fo group3, significant reduction in serum calcium in group1 (92.32 ± 10.94 µg/dl) vs. group 2 & 3 (122.9 ± 8.49 µg/dl & 130.92 ± 3.91 µg/dl), significant increase in serum magnesium in groupl (59.9 ± ll.18 µg/dl) vs. group 2 & 3 (37.71 ± 4.92 µg/dl & 38.71 ± 1 .4 µg/dl), significant reduction in Ca/Mg ratio in group1 (l.58 ± 0.33) vs group 2 & 3 (3.31 ± 0.49 & 3037 ± 0.07), significant increase in serum copper in group1 (4.83 ± 1.49 µg/dl) vs group 2 (2.64 ± 0.42 µg/dl) and group 3 (2.09 ± 0.68 µg/dl) and significant reduction in serum zinc in group l (1.47 ± 0.49 µg/dl) vs group 2 (3.15 ± 0.46 µg/dl) & group 3 (3.94 ± 1.52 µg/dl). The significance and pathogenic mechanisms of these abnormalities are explained.